The significance of acorns in Don Quixote. Issue 2 (2nd April 2020) - Darrell, Jennifer A.
Abstract: In the Barataria episode of Don Quixote, Cervantes uses acorns as a source of humor, highlighting the contrast between aristocratic and peasant ways of life. Acorns, however, not only connote a rustic, lower class existence, but they also symbolize the myth of the "Golden Age, " a romanticized vision of humanity's earliest days. Cervantes explicitly links acorns to the Golden Age earlier in the Quixote, when the nuts inspire don Quixote's discourse on the theme. While critics often interpret Barataria as a type of utopia, albeit a failed one, the symbolic connections that the acorns provide suggest that we should also read the episode against the myth of the Golden Age in order to uncover its full significance. A utopian society achieves its ideal state through adherence to a set of rules and regulations that aim to promote accord among its citizens, whereas this social code is absent in the Golden Age, unnecessary in an as-yet-uncorrupted community. Through his strategic use of acorns, Cervantes calls attention to the differences between the two visions of a halcyon existence, ultimately suggesting that the very idea of utopia points to a decline in the human condition.